Design of a Meander Line Monopole Antenna Array Based Hilbert-Shaped Reject Band Structure for MIMO Applications. Issue 4 (4th July 2022) - Al-Dulaimi, Zainab; Elwi, Taha A; Atilla, Dogu Cagdas
ABSTRACT: In this paper, a meander monopole antenna array based electromagnetic band gap (EBG) structure is proposed for MIMO applications. For this, two monopoles of a meander structure are printed on an FR4 substrate of 1.6 mm thickness and fed with 50Ω microstrip lines. The ground plane is defected with EBG Hilbert shaped inclusions of the 3rd order on the substrate back profile within a limited array size. This is achieved by having a negative refractive index (NRI) to reflect the surface waves totally away from the space filling between the antenna elements. Such property occurs only when the EBG defect operation is combined with the EBG slots. To realize the proposed design performance, a Finite Integral Technique (FIT) of CST Microwave Studio (CSTMWS) numerical analysis is invoked. Nevertheless, another numerical simulation based on Finite Element Method (FEM) based HFSS simulations is conducted to validate the regarded results. The proposed antenna design is fabricated to achieve excellent matching bandwidths, S 11 <−10 dB, around 2.45 GHz. The proposed antenna radiation pattern is found in the side direction of the array with a gain of 2.1dBi at 2.45 GHz. The proposed antenna axial ratio (AR) is tested and found to be below 3 dB at 2.45 GHz; that makes the antenna subject for circularly polarized radiator. Such achievement is attributed to the effect the fractal structure additions. Finally, the maximum mutual coupling between the antenna elements within a distance of 0.16λo at 2.45 GHz is bellow −30 dB at the two frequency bands of interest.